A history of collaboration between electrophysiologists and arrhythmia surgeons. - Cox, James L.; Churyla, Andrei; Malaisrie, S. Chris; Kruse, Jane; Kislitsina, Olga N.; McCarthy, Patrick M. (Journal of Cardiovascular Electrophysiology, 2022)
Introduction: The notion that medically‐refractory arrhythmias might one day be amenable to interventional therapy slowly began to appear in the early 1960's. At that time, there were no "interventional electrophysiologists" or "arrhythmia surgeons" and there was little appreciation of the relationship between anatomy and electrophysiology outside the heart's specialized conduction system. Methods: In this review, we describe the evolution of collaboration between electrophysiologists and surgeons. Results: Although accessory atrio‐ventricular (AV) connections were first identified in 1893 and the Wolff‐Parkinson‐White (WPW) syndrome was described 37 years later (1930), it was another 37 years (1967) before those anatomic AV connections were proven to be responsible for the clinical syndrome. The success of the subsequent surgical procedures for the WPW syndrome, AV node reentry tachycardia, automatic atrial tachycardias, ischemic and non‐ischemic ventricular tachycardias and atrial fibrillation over the next two decades depended on a close, sometimes daily, collaboration between electrophysiologists and surgeons. In the past two decades, that tight collaboration was largely abandoned until the recent introduction of "hybrid procedures" for the treatment of atrial fibrillation. Conclusions: A retrospective assessment of the 50 years of interventional therapy for arrhythmias clearly demonstrates the clinical benefits of a close collaboration between electrophysiologists and arrhythmia surgeons, regardless of which one is actually performing the intervention.